Gestörte Geweberegeneration durch entzündliche Prozesse bei Alterung, Seneszenz und degenerativen Erkrankungen – Interaktionen mit dem COVID-19-induzierten Zytokin-Sturm des angeborenen Immunsystems - Jakob, Franz; Herrmann, Marietta (Osteologie, 2022)
Entzündung ist Bestandteil einer jeglichen Geweberegeneration. Verletzung und Schädigung von Geweben - inklusive exogene virale und bakterielle Infektionen - induzieren eine frühe pro-inflammatorische Phase, die durch Aktivierung von residenten und aus dem peripheren Blut und Knochenmark rekrutierten Zellen des angeborenen Immunsystems weiter propagiert wird. Diese Phase dient auch dem Clearing der Umgebung von vorgeschädigten Zellen und cell debris. Um eine erfolgreiche Geweberegeneration zu erreichen ist es essentiell, die Auflösung der Entzündung durch zeitgerechte Einleitung einer anti-inflammatorischen Phase der Geweberegeneration zu ermöglichen. Dieser Phase kann dann die Gewebeneubildung folgen, am Beispiel der Frakturheilung als „Modeling“ bezeichnet. Das schnell gebildete neue Gewebe wird in der letzten Phase der Regeneration an die physikalischen Bedingungen im Gewebeverband angepasst, bei der Frakturheilung „Remodeling“ genannt. Kann die zeitgerechte Auflösung der Entzündung nicht erfolgen, verhindert die persistierende Entzündung das Eintreten in die Phase der Gewebeneubildung und damit die erfolgreiche Regeneration. Es erfolgt dann entweder als „Notlösung“ eine Narbenheilung oder im Falle weiter ausufernder Entzündung eine Zerstörung des Gewebes. Die mit dem Alter sich verschlechternde Regenerationskapazität vieler Gewebe inklusive Knochen, Muskel und Sehnen ist unter anderem eine Folge der subklinischen chronischen Entzündung von Geweben, die Alterung („Inflammaging“) propagiert. Die Entzündung im Mikromillieu involviert neben den gewebe-typischen Zellen und deren adulten Progenitoren auch die Zellen des gewebeeigenen (residenten) angeborenen Immunsystems, allen voran Makrophagen. Auch diese unterliegen Alters-assoziierten Veränderungen wie Zellalterung und eine gesteigerte Suszeptibilität für pro-inflammatorische Überreaktionen. Chronische Inflammation mündet letztlich in die zelluläre Seneszenz, die begleitet ist von einem Seneszenz-assoziierten sekretorischen Phänotyp (SASP) mit hoher Produktion von Interleukinen 1, 6, 8, und anderen Zytokinen. Solange solche Zellen nicht in den geregelten Zelltod gehen, unterhalten sie die chronische Entzündung und damit die Voraussetzungen für insuffiziente Geweberegeneration. Eine COVID-19 Infektion triggert und unterhält identische inflammatorische Mechanismen und induziert zusätzlich Seneszenz. Dies kann in der Summe zu einem Zytokin-Sturm führen, der in einem circulus vitiosus eine zerstörerische Hyperinflammation unterhält und der umso schwerwiegender ausfällt je höher die Vorlast an seneszenten Zellen ist, wie das in den COVID-Risikopopulationen der Fall ist. Deren Zusammensetzung überlappt sehr stark mit unseren Risikopopulationen für degenerative muskuloskelettale Erkrankungen wie Osteoporose und Sarkopenie.Inflammation is a component of any tissue regeneration. Injury and tissue damage - including exogenous viral and bacterial infections - induce an early pro-inflammatory phase, which is further propagated by activation of both resident innate immune cells and cells recruited from peripheral blood and bone marrow. This pro-inflammatory stage is essential for clearance of cellular debris and to induce the regenerative process. However, to achieve successful tissue regeneration, it is essential to allow timely resolution of inflammation by initiation of an anti-inflammatory phase of tissue regeneration. This phase can then be followed by new tissue formation, referred to as “modeling” in the example of fracture healing. The rapidly formed new tissue is adapted to the physical needs in the final phase of regeneration, called “remodeling” in case of fracture healing. If timely resolution of inflammation is missing, persistent inflammation prevents entry into the phase of new tissue formation and thus successful regeneration. Either scar healing occurs as a "stopgap" solution or tissue destruction is initiated.The deteriorating regenerative capacity of many tissues with age, including bone, muscle and tendon, occurs as a consequence of subclinical chronic inflammation of tissues that propagates aging (“inflammaging”). Inflammation in the micromillieu involves not only tissue-typical cells and their adult progenitors, but also the cells of the tissue’s resident innate immune system, above all macrophages. These are also subject to age-associated changes such as cellular aging and increased susceptibility to pro-inflammatory overreactions. Chronic inflammation ultimately leads to cellular senescence, which is accompanied by a senescence-associated secretory phenotype (SASP) with high production of interleukins 1, 6, 8, and other cytokines. As long as such cells do not enter regulated cell death, they maintain chronic inflammation, setting the stage for insufficient tissue regeneration.Inflammation can be self-sustaining in certain pathology and, in the worst case, can progress to a state of hyperinflammation that abolishes any regeneration, destroys tissue, and leads to tissue/organ failure. The best known example may be the highly active autoimmune hyperinflammation like in unmanaged rheumatoid arthritis. Infection with COVID-19 can cause a deleterious outcome of the disease with the same mechanism of hyperinflammation of the innate immune system. Here, hyperinflammation may exaggerate relatively independent of viral replication. COVID-19 directly stimulates NFkB-dependent pro-inflammatory secretion and initiates an IL6-dependent vicious circle, which is then amplified via innate immune system cells. COVID-19 also directly stimulates the so-called inflammasome of the cell. The virus also causes cellular senescence in this pro-inflammatory environment. Depending on the preload of senescent cells amenable to overstimulation for cytokine production, the greater the risk of a cytokine storm with a deleterious outcome. People of advanced age and those with chronic diseases accompanied by pro-inflammatory conditions such as severe obesity, diabetes, and arthritis consequently represent the high-risk populations for COVID-19 infection with a severe outcome. Of note, our target population for the treatment of osteoporosis and osteoarthritis meets this profile.In addition to antiviral therapeutic measures, it is equally important to address the mechanisms of hyperinflammation that result from, among other causes, the large preload and the additional senescent cells caused by COVID-19. We obviously have parallels that lie in the pathogenesis of tissue degeneration. It has been shown in animal models that osteoporosis responds to treatment with senolytics, and a clinical trial is underway. Severe COVID-19 infection was also significantly ameliorated by senolytics in animal models. Overall, it is of importance for physicians active in osteology to understand the interrelationships in the development of the high risk of severe COVID-19 disease in our elderly patient cohorts, and also to consider the consequences of severe COVID-19 disease. We also urgently need to pay attention to what e. g. long-covid disease means for existing and emerging musculoskeletal conditions such as osteoporosis and sarcopenia due to prolonged absolute and relative immobilization during the acute and rehabilitation phases.
Keywords: Entzündung; Gewebe-Regeneration; Osteoporose; Arthrose; COVID19-induzierter Zytokin-Sturm